Territorial Movements of Black-throated Blue Warblers in a Landscape Fragmented by Forestry. - Reed, J. Michael.; Harris, Rebecca J. (Tufts University. Tisch Library., 2016)
Many forest bird species show inhibition to entering open areas, including crossing habitat gaps. We examined the responses of Black-throated Blue Warblers (Dendroica caerulescens) to conspecific song playback within forest, at clearcut-forest ecotones, and across logging roads to assess movements of this Neotropical migrant into open areas. Males responded readily to song playbacks in all areas, and moved significantly farther into clearcuts than they did within intact forest (40.4 ± 2.9 m and 17.1 ± 1.2 m, respectively) Their singing, aggressive trilling, and alarm-calling rates were highest in response to playback from clearcuts, intermediate during road-crossings, and lowest within forest. Males moved farthest into the oldest regenerating clearcuts (>15 years old), indicating that vegetation structure also influences their movement into open areas. Second-year males were more responsive than older males, moving farther to reach speakers in all areas, and showing a nonsignificant trend of moving farther into clearcuts. We found that extensive movements into open areas occur in response to simulated territorial intrusion, indicating that small-scale habitat fragmentation by forestry may not disrupt territorial movements of that species.